Wearing Resistance of Metal Coating Layers after Laser Beam Heat Treatment - Olah Arthur; Machedon-Pisu Teodor; Viyureanu Petrica (MDPI Coatings, 2023)
Laser heat treatment (LHT) is applied herein after coating. Evaluation of the results was performed by studying the microstructures via metallographic SEM/EDX microscopy, and the mechanical properties were analyzed in terms of microscopic hardness and abrasion resistance. The objective of this study was to investigate the effect of LHT on the wear resistance of metal coatings. The results indicate the influence of the microstructure and chemical composition of the electrodes on the microhardness and wear resistance of the metal coatings (MCs).